2021
DOI: 10.21203/rs.3.rs-849340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stacked-origami mechanical metamaterial with tailored multistage stiffness

Abstract: Origami-baed metamaterial has shown remarkable mechanical properties rarely found in natural materials, but achieving tailored multistage stiffness is still a challenge. This study proposes a novel zigzag-base stacked-origami (ZBSO) metamaterial with tailored multistage stiffness property based on crease customization and stacking strategies. A high precision finite element (FE) model to identify the stiffness characteristics of the ZBSO metamaterial has been established, and its accuracy is validated by quasi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, the preceding discussion serves as a coarse approximation to designing a waterbomb tessellation with targeted mechanical properties. Related work that uses origami to achieve programmable stiffness includes Zhai et al [25] via curved crease origami, Wen et al [27] and Miyazawa et al [26] via stacked and cellular origami. In flat foldable, quadrilateral origami, it has been shown that the prescribing fold angles at the boundary uniquely determines the kinematics of the entire sheet [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the preceding discussion serves as a coarse approximation to designing a waterbomb tessellation with targeted mechanical properties. Related work that uses origami to achieve programmable stiffness includes Zhai et al [25] via curved crease origami, Wen et al [27] and Miyazawa et al [26] via stacked and cellular origami. In flat foldable, quadrilateral origami, it has been shown that the prescribing fold angles at the boundary uniquely determines the kinematics of the entire sheet [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Origami has emerged as an important platform in science and engineering for applications across a diverse array of length scales: from large-scale aerospace applications [1,2] to smaller-scale biomedical applications [3,4]. In particular, the multistability properties of origami have proven useful for the design of deployable structures that are stable in both their compact and deployed configurations [5,6], driving locomotion in origami-based robotics [710], storing mechanical energy [11] and information [1214], and for origami-based mechanical metamaterials[1527].…”
Section: Introductionmentioning
confidence: 99%
“…We then perform the novel NTO method to optimize an origami chomper-based flexible gripper to reassign the materials at the creases. Unlike the majority of previous works that regarded creases as straight or curved lines [70][71][72], this study contemplates the geometrical characteristics of creases. We fabricate the prototypes of the optimized origami chomper-based flexible gripper by a laser cutter, followed by testing various gripping performances, including gripping range capability under an identical input load, maximum gripping ratio, gripping adaptability, and achieving richer gripping characteristics by size scaling, demonstrating that the optimized origami chomper-based flexible gripper exhibits excellent gripping performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some representative works are as follows: Lv [ 24 ] and co-workers studied the mechanical properties of periodically-arranged Miura sheets and found that the Miura sheet model can achieve both positive and negative Poisson ratios, which is consistent with its shear behavior and infinite bulk elastic modulus; in this study, a Miura sheet was considered to be a rigid origami structure, i.e., during the folding process, the facets between creases were not allowed to deform. Since then, more and more researchers have studied the stiffness characteristics of non-periodic origami structures and their load-bearing capacity, demonstrating their exotic mechanical properties [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Liu et al [ 25 ] numerically and experimentally studied the deformation laws and energy-absorbing capacity of Miura sheets made of polymers under different loading conditions; the outcomes revealed that the dynamic properties of the Miura sheet can be broadly tailored.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, quasi-static in-plane compression of novel metamaterials, inspired by zig-zag folded origami structures, at large plastic strains were investigated by numerical and analytical methods; it was found that the proposed origami metamaterials outperformed the conventional Miura-ori based metamaterials, in terms of energy absorption [ 29 ]. Wen and co-workers [ 30 ] proposed a class of novel origami metamaterials based on crease customization and stacking strategies; they numerically and analytically uncovered the tailored multistage stiffness. Zhou et al [ 10 ] designed experiments to study the brace hysteretic behavior of a novel origami energy dissipation brace, formed by a combination of Miura and Tachi unit cells.…”
Section: Introductionmentioning
confidence: 99%